Thrombus aspiration in primary percutaneous coronary intervention in acute ST-elevation myocardial infarction patients with high thrombus burden: one-year outcomes in a tertiary healthcare center in Ho Chi Minh City - Duy Cao Phuong Le; Giang Thai Pham; Quan Duy Vo (The Egyptian Heart Journal)
Abstract Background Primary percutaneous coronary intervention (PCI) can dislodge atherosclerotic debris, risking microvascular embolism. Thrombus aspiration (TA) before stenting in ST-segment elevation myocardial infarction (STEMI) patients has been linked to reduced mortality, lower recurrence of heart attacks, and improved cardiac function. However, limited research exists on the effectiveness of TA in Vietnam, underscoring the need for further studies to enhance cardiovascular care. This prospective observational study was conducted to evaluate the role of TA in STEMI patients admitted with a substantial thrombus burden at Nguyen Tri Phuong Hospital. Results Out of 92 participants, 68 underwent TA treatment. Post-treatment, the TA group exhibited better TIMI and TMP flow grades and a higher rate of ST-segment normalization, with no significant difference in major adverse cardiac events (MACEs) at 30-day and 12-month follow-ups compared to those untreated. Conclusions TA during PCI enhances ST-segment normalization and TIMI and TMP scores in STEMI patients, improving myocardial perfusion. No difference in MACE occurrence was noted between groups after 30 days and 12 months, suggesting TA’s potential benefits without increasing adverse outcomes.